2016
DOI: 10.22146/agritech.16589
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Perendaman Asam Askorbat dan Natrium Bisulfit pada Dua Varietas Bawang Merah (Allium ascalonicum L.) terhadap Sifat Fisikokimia dan Organoleptik Tepungnya (Effect of Ascorbic Acid Soaking and Sodium Bisulphite on Two Varieties of Shallot (Allium ascalonicum L.) on Physical and Organoleptical Character of Shallot Powder)

Abstract: Recently, there is an increase of shallot production in Indonesia. One alternative of flesh shallot processing is shallot powder making which can be used during the off season. The aim of the study was to observe the effect of immersion in ascorbic acid and sodium bisulphite on two varieties of shallot on physical and organoleptic characters of shallot powder. Drying was done using tray dryer. Experimental design used was factorial completely randomised design. The first factor was the type of immersion agent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…It is most effective than other additives in preventing the green discoloration [6]. Some research result reported that sodium bisulphite can prevent discoloration of pumpkin powder [7] [8], banana [9], apple [9], potatoes [10], green coconut water [11], shallot [12] [13] [14], and garlic [6]. This study aimed to determine the effect of size reduction method and sodium bisulfite concentration on the characteristics of garlic powder from off-grade garlic.…”
Section: Introductionmentioning
confidence: 99%
“…It is most effective than other additives in preventing the green discoloration [6]. Some research result reported that sodium bisulphite can prevent discoloration of pumpkin powder [7] [8], banana [9], apple [9], potatoes [10], green coconut water [11], shallot [12] [13] [14], and garlic [6]. This study aimed to determine the effect of size reduction method and sodium bisulfite concentration on the characteristics of garlic powder from off-grade garlic.…”
Section: Introductionmentioning
confidence: 99%